Book Review: Henry L. Tischler (Ed.) (2000) Debating Points: Race and Ethnic Relations. - Young M. Kim (Networks: An Online Journal for Teacher Research, 2000)
Today's college students seem to care little about many important social issues on the public agenda. Their interest in such issues often appears to be at best minimal and sporadic, and consequently they are more likely to form and express superficial opinions on those matters. One exceptional case is the issue of race. The issue of race matters deeply to students, and most of them know where they stand on it.